RF & linearity distortion sensitivity analysis of DMG-DG-Ge pocket TFET with hetero dielectric. (February 2021) - Priyadarshani, Kumari Nibha; Singh, Sangeeta; Naugarhiya, Alok
Abstract: The incorporation of dual-metal, double-gate, germanium pocket and hetero gate dielectric tunnel field effect transistor (DMG-DG-Ge pocket TFET) allows the conceptualization and realization of suppressed ambipolarity. These deployed technology boosters for the TFET tailor the electric field as per the need at source-channel and drain-channel interfaces. The novelty of this work lies in its dual-metal and hetero dielectric structure that are introduced in Ge- pocket TFET structure. The major goal achieved here is enhanced I ON /I OFF ratio. Further using the exhaustive and calibrated TCAD analysis, this work examines the analog/RF and linearity distortion performance of DMG-DG-Ge pocket TFET. Here, intrinsic device capacitances, transconductance, cutoff frequency, transgeneration factor (TGF), higher order derivatives of drain current ( g m 2 and g m 3 ), VIP 2, VIP 3, IIP 3 and IMD 3 are being extracted. Effect of different device parameters: channel length, body thickness, oxide thickness and pocket width on the dc, analog/RF and linearity distortion parameters has also been studied. The present analysis reveals an in-depth guideline for the design of DMG-DG-Ge pocket TFET with optimized analog/RF performance with least linearity distortions.